2021
DOI: 10.26451/abc.08.02.04.2021
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Challenges in the Assessment of Dogs' (Canis lupus familiaris) Susceptibility of the Ebbinghaus-Titchener Illusion Using the Spontaneous Choice Task

Abstract: Visual illusions represent an innovative method to investigate animal visual perception. One well known geometric illusion is the Ebbinghaus-Titchener illusion, which consists of two identically sized target circles with one surrounded by large inducer circles and the other surrounded by small inducer circles. Humans are susceptible to this illusion, underestimating the size of the target circle surrounded by larger inducers and overestimating the size of the target circle surrounded by smaller inducers. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Realistically, selecting a testing method freely may not always be possible, as spontaneous testing might not be suitable for all species (e.g. [ 57 ] where it was suggested that spontaneous choice test may invoke an inhibitory control problem in dogs). Finally, both methodologies have the issue of evaluating visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…Realistically, selecting a testing method freely may not always be possible, as spontaneous testing might not be suitable for all species (e.g. [ 57 ] where it was suggested that spontaneous choice test may invoke an inhibitory control problem in dogs). Finally, both methodologies have the issue of evaluating visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…While it is possible that susceptibility was not observed, such contradictory results could be methodological in nature. Despite the spontaneous choice paradigm’s effectiveness in revealing illusory susceptibility via subjects’ attraction to perceived motion without the (potentially confounding) use of food, it is also known for its flaws [ 8 , 26 ]. Specifically, subjects may orient more to the illusion due to other factors (e.g., context of food reward) rather than perceived motion.…”
Section: Discussionmentioning
confidence: 99%